Complementarity and custom in wage contract violation - John S. Earle; Klara Sabirianova Peter (W.E. Upjohn Institute for Employment Research, 2006)
We analyze a model of wage delay in which strategic complementarity arises because each employer's costs of violating its contracts decrease with the arrears in its labor market. The model is estimated on panel data for workers and firms in Russia, facilitating identification through fixed effects for employees, employers, and local labor markets, and instrumental variables based on policy interventions. The estimated reaction function displays strongly positive neighborhood effects, and the estimated feedback loops - worker quits, effort, strikes, and legal penalties - imply that costs of wage delays are attenuated by neighborhood arrears. We also study a nonlinear case with two stable equilibria: a punctual payment and a late payment equilibrium. The estimates imply that the theoretical conditions for multiple equilibria under symmetric labor market competition are satisfied in our data.
Keywords: A12; B52; J30; K42; L14; O17; P31; P37; 330; contract violation; wage arrears; social custom; strategic complementarity; neighborhood effect; social interactions; multiple equilibria; network externality; transition; Russia; Lohn; Zahlungsmoral; Vertrag; Soziale Norm; Soziale Beziehungen; Gleichgewicht; Theorie; Russland